KOLABORASI STAKEHOLDERS DALAM PELAKSANAAN MANAJEMEN BERBASIS SEKOLAH DI SD NEGERI 21 PEMECUTAN - Chindytia; Bagus Gede Surya Abadi, Ida; Magfira, Raviza; Putu Vina Widiantari, Ni; Rahma Putri, Yuliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines stakeholder collaboration in the implementation of School Based Management (SBM) at SD Negeri 21 Pemecutan. The study is motivated by the gap between the expected optimal implementation of SBM and the empirical conditions, including limited infrastructure, uneven literacy achievement, and suboptimal documentation of school programs. The purpose of this study is to describe the implementation of SBM, identify the stakeholders involved, analyze the forms of collaboration, and determine the supporting and inhibiting factors. This research employs a qualitative approach with a case study design. Data were collected through interviews, observations, document analysis, and questionnaires involving the principal and a classroom teacher as key informants. The findings show that the implementation of SBM is in the “good” category, with an observation score of 75% and a questionnaire score of 82.19%. Stakeholder collaboration involves both internal and external parties, including the principal, teachers, students, parents, school committees, government, and universities. This collaboration supports school programs, particularly in literacy, numeracy, and character development. However, challenges remain in terms of limited facilities, uneven student achievement, and the need to strengthen community engagement. Therefore, improving stakeholder collaboration and optimizing resource management are necessary to enhance the effectiveness of SBM implementation.